OPTIMALISASI PENANGGULANGAN DAMPAK PANDEMI COVID-19 MELALUI PENDAMPINGAN MASYARAKAT DI DUKUH TESEH, WANGEN, POLANHARJO, KLATEN - Miftahul Jannah; Mufti Arief Arfiansyah (LPPM STAIMAS WONOGIRI, 2021)
The impact of the Covid-19 pandemic on society occurs in various fields, including social, economic, health, religious and educational. The education and health sectors are the main problems that are being felt by the people of Dukuh Teseh, Wangen, Polonharjo, Klaten. So that service is needed in the form of community assistance so that the impact of the Covid-19 pandemic can be handled properly. The method of service with the PAR (Participatory Action Research) approach is community service by conducting research, action and participatory. Community service by engaging directly in the community, analyzing problems, formulating problem solving, and carrying out service actions accompanied by citizen participation so that the implementation of service activities in Dukuh Teseh can run optimally, so that it produces results and is sustainable in the community. Community service is carried out by providing assistance in the field of education, namely learning assistance and TPA assistance, and in the health sector, namely socializing the dangers of COVID-19 and how to prevent it. The result of this service is that it has a positive impact on the residents of Dukuh Teseh, namely increasing residents' knowledge about Covid-19 so as to prevent the spread of Covid-19 and increase the enthusiasm of children in learning in the midst of the Covid-19 pandemic.